A hadronic transport analysis on the Δ mass in Au + Au reactions at 1.23 AGeV. Issue 9 (12th January 2020) - Reichert, Tom; Hillmann, Paula; Limphirat, Ayut; Herold, Christoph; Bleicher, Marcus
Abstract: This study is motivated by upcoming data from the high acceptance di‐electron spektrometer (HADES) collaboration at gesellschaft für schwerionenforschung, which presented preliminary data on a possible mass shift of the Δ(1232) resonance in central Au + Au reactions at E lab = 1.23 AGeV. This effect is explored via the Ultra Relativistic Quantum Molecular Dynamics transport model, allowing us to track down each decaying Δ(1232) resonance and check whether it can be reconstructed. The obtained results show that the apparent mass shift on the order of 50 MeV can be explained by a late‐stage formation effect and a long‐evolving Δ ↔ N + π cycle.